Pharmacological aspects of application of 1,2,4-triazole-3-thiol furan derivatives - O. A. Bihdan; V. V. Parchenko; О. І. Panasenko; E. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Introduction. Nowadays 1,2,4-triazole-3-thiol furan derivatives have established themselves as a separate class of promising bioactive compounds. Presented substance is practically non-toxic and exhibits various kinds of pharmacological activity. New original drug «Tryfuzol» in two dosage forms (1% injectable solution and 1% solution for oral administration) triumphantly entered the practice of the national veterinary. The most attractive in pharmacological aspects are water-soluble compounds 5-(furan-2-yl)-4R-1,2,4-triazole-3-thiols. Other classes of 1,2,4-triazole-3-thiol furan derivatives are also in considerable scientific interest. However, despite the presence of a sufficiently large number of publications, the issue of pharmacological tests systematization of the 1,2,4-triazole-3-thiol furan derivatives is still open.